RELATIONSHIP OF METABOLIC SYNDROME COMPONENTS WITH ELECTROCARDIOGRAPHIC BIOMARKERS OF METABOLIC CARDIOMYOPATHY IN MEN WITH CORONARY ATHEROSCLEROSIS - Yu. I. Ragino; N. A. Timoshenko; A. M. Chernjavskyi; S. Yu. Tcimbal; L. V. Scherbakova; M. I. Voevoda (Российский кардиологический журнал)
Aim. To study electrocardiographic (ECG) markers of metabolic cardiomyopathy (MC) and their association with the components and markers of metabolic syndrome (MS) in men with coronary atherosclerosis (CA). Material and methods. Totally 77 men included at the age 42-77 with stenotic CA verified by coronary angiography (CAG), without acute coronary syndrome (ACS) with stable angina (II-IV FC) — inhabitants of the Western Siberia. All patients underwent the recording of resting ECG in 12 standard leads with following coding by Minnesota code. The ECG markers of MC were studied as the QT duration, corrected QX ST segment shift above isoline for more than 0,5 mm, ST depression below isoline >0,5 mm of nonischemic type, T wave changes (platening and amplitude decrease), inversion, TV1>TV6 syndrome (amplitude of T in V1 is higher than T in V6), signs of left ventricle hypertrophy (LVH), rhythm and conduction disorders. In all patients we also assessed the components of MS as waist circumference, body mass index, systolic and diastolic arterial pressure (SBP, DBP),levels of total cholesterol (TC), low and high density lipoprotein cholesterol (LDL, HDL), C-peptide, glucose.Results. In men with CA there were following ECG markers of MC found: arrhythmias in 38 patients, LVH in 55, TV1>TV6 in 24, Twave changes in 58, ST elevation in 44, ST depression in 23, prolonged QT in 5. MS in general in the group studied was found in 80,5% of men. The positive correlation was found for the length of QT and SBP values, for ECG signs of LVH with increased levels of TC, for increased C-peptide and ST depression. In the group of the patients with CA and increased C-peptide level relative risk of ST depression was 3,3 times more than in patients with normal C-peptide. In the group of CAand increased LDL relative riskof ECG signs of LVH was 3,8 times more than in CAand normal LDL.Conclusion. Therefore the presence in coronary atherosclerosis of MS and its constituents is associated with the presence of some ECG biomarkers of MC that shows the partial similarity of the influences of metabolic disorders on development of the diseases.